The relationship between basketball shooting kinematics, distance and playing position - Miller, S.; Bartlett, R. (Journal of Sports Sciences, 1996)
Three-dimensional cinematography (100 Hz) was used to establish the relationship between distance and the kinematics of shooting with respect to playing position in basketball. Fifteen subjects, divided into guards, forwards and centres (all n = 5), performed jump shots from each of three distances: 2.74, 4.57 and 6.40 m from the basket. Increases in mean release speed were found as shooting distance increased for all groups. This was due to increased angular velocities of both shoulder flexion and elbow extension and an increased speed of the centre of mass in the direction of the basket. Release angles for the two shorter distances (52-55°) tended to provide the advantage of a steep angle of entry into the basket, whereas those at the longest distance (48-50°) were closer to those requiring the minimum possible release speed. All groups exhibited an earlier timing of release as shooting distance increased, which gave rise to an earlier rotation of the shoulder axis. The more consistent changes in kinematic patterns with changes in shooting distance exhibited by guards as compared to centres would suggest that such adjustments are easier to make for those players who regularly shoot from long range.